Profiling of Indigenous Biosurfactant-Producing Bacillus Isolates in the Bioremediation of Soil Contaminated by Petroleum Products and Olive Oil - Paola Sandra Elenga-Wilson; Christian Aimé Kayath; Nicaise Saturnin Mokemiabeka; Stech Anomene Eckzechel Nzaou; Etienne Nguimbi; Gabriel Ahombo (International Journal of Microbiology)
Petroleum is, up to this date, an inimitable nonrenewable energy resource. Petroleum leakage, which arises during transport, storage, and refining, is the most important contaminant in the environment, as it produces harm to the surrounding ecosystem. Bioremediation is an efficient method used to treat petroleum hydrocarbon-contaminated soil using indigenous microorganisms. The degradation characteristics for a variety of hydrocarbons (hexane, benzene, gasoline, and diesel) were qualitatively and quantitatively investigated using Bacillus isolates. Microbiological and biochemical methods have been used including isolation of oil-degrading bacteria, enzymatic activities, the determination of physicochemical parameters, biosurfactant production and extraction assay, oil displacement assay, antimicrobial assay of the biosurfactants, and bioremediation kinetics. Consequently, of the 60 isolates capable of degrading different hydrocarbons at fast rates, 34 were suspected to be Bacillus isolates capable of growing in 24 h or 48 h on BH medium supplemented with 2% of hexane, benzene, gasoline, diesel, and olive oil, respectively. Among the 34 isolates, 61% (21/34) are capable of producing biosurfactant-like molecules by using gasoline, 70% (24/34) with diesel oil, 85% (29/34) with hexane, and 82% (28/34) with benzene. It was found that biosurfactant-producing isolates are extractable with HCl (100%), ammonium sulphate (95%), chloroform (95%), and ethanol (100%). Biosurfactants showed stability at 20°C, 37°C, 40°C, and 60°C. Biosurfactant secreted by Bacillus strains has shown an antagonistic effect in Escherichia coli, Shigella flexneri 5a M90T, and Bacillus cereus. The selected isolates could therefore be safely used for biodegradation. Substrate biodegradation patterns by individual isolates were found to significantly differ. The study shows that benzene was degraded faster, followed by hexane, gasoline, and finally diesel. The Bacillus consortium used can decrease hydrocarbon content from 195 to 112 (g/kg) in 15 days.